Eco-pedagogy - Yasida, Khaliq Setya (Sebelas Maret University (UNS), 2020)
AbstractEcopedagogy is a method that takes into account the environment which is considered regarding ecological awareness. Comprehensive education about nature can increase a sense of concern for the environment where it is necessary to exploit more natural resources that can damage, as well as discussing history in the ecological environment, students can better understand nature as something useful and important. received is that which is fun, preserving, and loves nature and its life.Keyword: Ecopedagogy, Education, Nature, History